2016
DOI: 10.4172/2161-0517.1000154
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combretum molle Seed Extracts on the Growth of the Mycelial Form of Histoplasma capsulatum Var Farciminosum-an In Vitro Trial

Abstract: Epizootic lymphangitis (EL) compromises the welfare of working horses and has a serious negative impact on the livelihoods of cart horse owners/drivers in the affected parts of Ethiopia. Unfortunately, antifungal drugs for the treatment of EL are unavailable in both private and government clinics. The spread of multidrug-resistant strains of fungi motivates to discover new classes of antifungal compounds that inhibit these resistant strains. Therapeutic alternative compounds, particularly those isolated from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…The different parts of the studied plant have been scientifically approved to have different pharmacological activities such as anti-inflammatory, 16 antischistosomal, anthelmintic, 17 antimicrobial, 18,19 and antifungal activities. 20,21 The antiplasmodial activity of the seed (in vivo) and stem bark (in vitro) extract had also been approved pharmacologically. 22,23…”
Section: Introductionmentioning
confidence: 99%
“…The different parts of the studied plant have been scientifically approved to have different pharmacological activities such as anti-inflammatory, 16 antischistosomal, anthelmintic, 17 antimicrobial, 18,19 and antifungal activities. 20,21 The antiplasmodial activity of the seed (in vivo) and stem bark (in vitro) extract had also been approved pharmacologically. 22,23…”
Section: Introductionmentioning
confidence: 99%
“…This has been examined to assure the plants efficacy in treating disease by some researchers. For instance an in-vitro study conducted by [6] indicated that fresh garlic extract has some degree of growth inhibitory effect on the mycelial form of Histoplasma capsulatum var Farciminosum [16] has conducted evaluation of berries of phytol accado decandra for growth inhibition of Histoplasma capsulatum var Farciminosum and treatment of cases of epizootic lymphangitis in Ethiopia and that was effective. The works mentioned above are good indicators that Xanthium Strumarium leaf extract may have a potent inhibitory effect on Histoplasma capsulatum var Farciminosum (HCF).…”
Section: Ethnomentioning
confidence: 99%
“…The yeast form of the fungus is found in the infected host and the mycelial saprophytic stage in the environment [3,5]. Epizootic lymphangitis has a serious negative impact on the livelihoods of cart horse owners/drivers in the affected areas and also compromises the welfare of working horses [6]. The disease is endemic in countries bordering the Mediterranean, particularly in Italy and North Africa and is also found in Central and Southern Africa, and in regions of Asia and Russia [4].…”
Section: Introductionmentioning
confidence: 99%